2012
DOI: 10.1016/j.carbpol.2012.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a new dextran with a low degree of branching produced by Leuconostoc mesenteroides FT045B dextransucrase

Abstract: This paper offers the physical and chemical characterization of a new dextran produced by Leuconostoc mesenteroides FT045B. The chemical structure was determined by Fourier Transform Infrared spectroscopy and 1 H Nuclear Magnetic Resonance spectroscopy. The dextran was hydrolyzed by endodextranase; the products were analyzed using thin layer chromatography and compared with those of commercial B-512F dextran. The number-average molecular weight and degree of polymerization of the FT045B dextran were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…In a previous study, the -1,6-glycosidic linkage in the main chains was demonstrated at a peak of 4.93 ppm, whereas -1, 3-glycosidic link-age in the branch is located at approximately 5.20 ppm (Gan et al, 2014). Similar results have been reported by other authors (Seymour et al, 1979;Vettori et al, 2012;Dong et al, 2013).…”
Section: H Nmrsupporting
confidence: 93%
See 2 more Smart Citations
“…In a previous study, the -1,6-glycosidic linkage in the main chains was demonstrated at a peak of 4.93 ppm, whereas -1, 3-glycosidic link-age in the branch is located at approximately 5.20 ppm (Gan et al, 2014). Similar results have been reported by other authors (Seymour et al, 1979;Vettori et al, 2012;Dong et al, 2013).…”
Section: H Nmrsupporting
confidence: 93%
“…05, 97.70, 73.39, 71.39, 69.18 and 65.53 ppm (Figures 8 a and b), which was a characteristic of linear dextran. The major resonance in the anomeric region occurs at 97.70 ppm showed that the C-1 is linked (Vettori et al, 2012). Another intense signal at 62.65 confirmed that most of C-6 were also linked, and this proved that glucose residues in dextran were linked by -(1,6) glycosidic bond.…”
Section: Nmrmentioning
confidence: 84%
See 1 more Smart Citation
“…S1), its number-average molecular weight (M n ) and molecular weight distribution (M w /M n ) were determined to be 33,489 and 1.55, respectively. By 1 H NMR analysis (Benzeval, Bowyer, & Hubble, 2012;Pasika & Cragg, 1963;Vettori, Franchetti, & Contieroa, 2012), its degree of ␣-(1,3)-linked branching was found to be 5.0% (Fig. S2).…”
Section: Methodsmentioning
confidence: 93%
“…67 It has been used therapeutically as a blood thinner to decrease thrombosis. 6 Microstructured dextran-based hydrogels that significantly reduced the burst effect in releasing the PEGylated protein drug interferon-α2a were reported by Bae et al; microstructured PEG domains carrying the protein drug were dispersed throughout a bulk dextran hydrogel.…”
Section: Polymers Commonly Used For Microgelsmentioning
confidence: 99%